Jews and Germans : promise, tragedy, and the search for normalcy - Lewy, Guenter, 1923- (University of Nebraska Press ; The Jewish Publication Society, 2020)
Jews and Germans is the only book in English to delve into the history and challenges of the German-Jewish relationship from before the Holocaust through today. Were the Weimar Republic years (1918 - 1933) truly reciprocal for Jews and Germans? Post- Holocaust, how has that complex relationship evolved?"--